2018
DOI: 10.1016/j.jshs.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rhodiola rosea supplementation on mental performance, physical capacity, and oxidative stress biomarkers in healthy men

Abstract: PurposeThe objective of this study was to investigate the effects of chronic Rhodiola rosea (R. rosea) supplementation on mental and physical performance, as well as hormonal and oxidative stress biomarkers.MethodsTwenty-six healthy male students received either R. rosea extract (600 mg/day; RR) or placebo (PL) in a randomized double-blind trial. Prior to supplementation (Term I) and following 4 weeks of supplementation (Term II), the students underwent psychomotor tests for simple and choice reaction time, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(77 citation statements)
references
References 30 publications
(55 reference statements)
2
69
0
6
Order By: Relevance
“…Under these conditions, the body consumes a large number of energy-producing substances. These substances subsequently activate the hypothalamus-pituitary gland-adrenal gland axis, intensifying cortisol production [34]. Cortisol was positively correlated with serum hydrocortisone (r = 0.536, p < 0.05) and L-arabinono-1,4-lactone (r = 0.469, p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, the body consumes a large number of energy-producing substances. These substances subsequently activate the hypothalamus-pituitary gland-adrenal gland axis, intensifying cortisol production [34]. Cortisol was positively correlated with serum hydrocortisone (r = 0.536, p < 0.05) and L-arabinono-1,4-lactone (r = 0.469, p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive oxidative stress is linked to reduced muscle performance along with mental fatigue [57][58][59]. In addition, higher plasma and skeletal muscle antioxidant levels have been shown to attenuate both physical and mental fatigue [60,61]. Glutamine is thought to increase the antioxidant defense systems via the antioxidant properties of the amino acid or due to its conversion to glutathione [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…In this instance a higher dose (1600 mg) was less effective [ 222 ]. Single, placebo-controlled studies also demonstrated that Withania somnifera extract, which contains triterpene withanolides, administered for 60 days could improve attention, executive function and memory [ 223 ], and that Rhodiola rosea extract, which contains salidrosides, could increase the speed and accuracy of two attention tasks [ 224 ].…”
Section: Terpenesmentioning
confidence: 99%